Home Garden Areas (KRPL) and Food Insecurity in Indonesia - Yudistira, Giskar; Susanti, Hera (Jayapangus Press, 2026)
Food security is essential to ensure the availability, access, and consumption of sufficient, nutritious, and safe food for all people. The Home Garden Areas or Kawasan Rumah Pangan Lestari (KRPL) in the local language is one of the government's food security programs. The number of KRPLs has steadily increased between 2017 and 2021. However, the level of food insecurity has risen since 2020. Variations in the number of KRPLs from 2017 to 2021 were accounted for in this study to estimate their impact on food insecurity. This study recommends that KRPL be accompanied by other policies, particularly poverty reduction programs in food insecurity interventions, at least in regencies/municipalities with